Sebuah Studi Komparatif Tindak Pidana Perzinahan dalam Qanun Aceh dan KUH Pidana di Indonesia - Syahrul -; Mukhtaruddin (Program Pascasarjana IAIN Langsa, 2022)
This study examines a comparative study of the crime of adultery in Aceh Qanun Number 6 of 2014 concerning the Jinayat Law and Article 284 of the Criminal Code which applies as positive law in Indonesia. From the results of the study it was found that the comparison between the two laws lies in the elements of the crime of adultery, sanctions and procedures for applying the law to the perpetrators of the crime of adultery. In Aceh Qanun Number 6 of 2014 concerning the Jinayat Law, the adulterer was handed down 'Uqubat Hudud lashes one hundred times for married (muhsan) and unmarried (ghairu muhsan) adulterers. Meanwhile, in Article 284 of the Criminal Code, a maximum prison sentence of nine months is imposed on adulterers who are already bound in marriage.